1976
DOI: 10.3109/17453677608988751
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Strength After Major Amputation of the Sacrum:An Experimental Study

Abstract: Major sacral resections up to the level of S 1 and even higher have been performed. This has raised the question of the degree to which such operations weaken the pelvic ring. Fifteen cadaver pelves, including the fifth lumbar vertebra, were loaded to failure, five unresected, five after resection of the sacrum between S 1 and S 2, and five after resection about 1 cm below the promontory. The weakening of the pelvic ring amounted to approximately 30 per cent with the former type of resection and 50 per cent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(74 citation statements)
references
References 7 publications
2
71
0
1
Order By: Relevance
“…Patients who were certain to lose bowel control because of S2 nerve roots involvement also had a combined approach with colostomy formation. Lumbosacral stabilization was performed when greater than 50% of either sacroiliac joint was resected, as this destabilizes the pelvis [16]. The anterior procedure is performed by a general surgeon through a midline laparotomy incision.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who were certain to lose bowel control because of S2 nerve roots involvement also had a combined approach with colostomy formation. Lumbosacral stabilization was performed when greater than 50% of either sacroiliac joint was resected, as this destabilizes the pelvis [16]. The anterior procedure is performed by a general surgeon through a midline laparotomy incision.…”
Section: Methodsmentioning
confidence: 99%
“…Bone wax is used for the bony elements. Spinopelvic reconstruction with rods and pedicle screws is performed when required [16]. The omentum then is pulled through and laid across the defect posteriorly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that a negative surgical margin is the most important predictor of the local recurrence rate and survival [3,12,13,44]; however, wide resection is not achieved in 35% to 75% of patients undergoing surgery for this diagnosis [42]. Surgery in this anatomic site is challenging as a result of the complexity of the pelvic anatomy, adjacent visceral and vascular structures, and frequent compromise of spinopelvic continuity [12,17,32]. Surgeons often face a difficult choice between maximizing the preservation of function and achieving an adequate surgical margin.…”
Section: Introductionmentioning
confidence: 99%
“…29 Gunterberg and colleagues 25,27 studied the biomechanical effects of transverse partial sacrectomy using a cadaveric model with an axial load applied to the lumbosacral junction. In those studies, transverse amputations of the proximal sacrum, especially those that involve the sacral ala, significantly weakened the ability of the spinopelvic segment to resist vertical loading.…”
Section: 53mentioning
confidence: 99%